Digestibility of energy, amino acids, and phosphorus in a novel source of soy protein concentrate and in soybean meal fed to growing pigs - Oliveira, M. S. [UNESP]; Stein, H. H. (Amer Soc Animal Science, 2016)
Three experiments were conducted to determine standardized ileal digestibility (SID) of CP and AA, DE and ME, and apparent total tract digestibility (ATTD) and standardized total tract digestibility (STTD) of P in a new source of soy protein concentrate (SPC) and in soybean meal (SBM). In Exp. 1, 9 barrows (initial BW: 13.08 +/- 1.98 kg) were prepared with a T-cannula in the distal ileum and allotted to a triplicated 3 x 3 Latin square design with 3 diets and 3 periods. A nitrogen-free diet and 2 diets that contained corn starch and SPC or SBM as the sole source of CP and AA were formulated. Each period lasted 7 d, and ileal digesta were collected on d 6 and 7 of each period. The SID for Ile, Leu, Phe, Pro, and Tyr was greater (P < 0.05) in SPC than in SBM, but for CP and all other AA, no difference between SPC and SBM was observed. In Exp. 2, 24 barrows (initial BW: 13.94 +/- 1.34 kg) were housed individually in metabolism crates and randomly allotted to 1 of 3 diets. A corn-based diet (96.9% corn) and 2 diets that contained corn and SPC or corn and SBM were formulated. Each diet was fed to 8 pigs. Feces and urine samples were collected using the marker to marker method with 5-d adaptation and 5-d collection periods. The DE and ME in SPC and SBM were calculated using the difference procedure. Results indicated that the ATTD of GE was lower (P < 0.05) in SBM than in corn and the DE and ME in SPC were greater (P < 0.01) than in corn and SBM. In Exp. 3, 40 barrows (initial BW: 14.12 +/- 2.08 kg) were placed in metabolism crates and allotted to 4 diets in a randomized complete block design with 10 pigs per diet. Two diets were based on SPC or SBM as the sole source of P. Two additional diets were formulated by adding microbial phytase to diets that were otherwise similar to the 2 initial diets. Feces were collected for 5 d after a 5-d adaptation period and values for ATTD and STTD of P were calculated. No differences were observed in ATTD and STTD of P between SPC and SBM, but the ATTD and STTD of P of both SPC and SBM were greater (P < 0.01) if microbial phytase was added to the diets. In conclusion, the concentrations of DE and ME are greater in SPC than in SBM, but the SID of most AA and the STTD of P are not different between SPC and SBM.
Keywords: amino acid digestibility; energy; phosphorus digestibility; pigs; soybean meal; soy protein concentrate